Distinct structural mechanisms of LGR4 modulation by Norrin and RSPOs in Wnt/β-catenin signaling - Huarui Qiao; Fangzheng Hu; Yiang Wang; Lu Wang; Siyu Zhou; Shaojue Guo; Yiwen Xu; Jianfeng Xu; Qianqian Cui; Qilun Yang; H. Eric Xu; Jianwei Zhu; et al. (Nature Communications)
Abstract The Wnt/β-catenin pathway requires precise regulation for proper development and tissue homeostasis, yet the structural mechanisms enabling its fine-tuned control remain incompletely understood. Here, we reveal how LGR4 achieves differential signaling outcomes through distinct recognition of two key modulators: Norrin and R-spondins (RSPOs). Using cryo-electron microscopy, we determined the structure of full-length LGR4 bound to Norrin in a 2:2 stoichiometry, revealing a molecular bridging mechanism where Norrin dimer connect two LGR4 protomers in a spatial arrangement fundamentally distinct from the LGR4-RSPO2-ZNRF3 complex. Notably, Norrin binding to LGR4 sterically hinders simultaneous interaction with the Frizzled4 receptor, establishing a regulatory checkpoint in Wnt signaling. The partially overlapping binding sites for Norrin and RSPOs on LGR4 enable mutually exclusive interactions that drive distinct signaling outcomes. Disease-linked mutations map to distinct functional regions: those disrupting LGR4 interaction are associated with familial exudative vitreoretinopathy (FEVR), while others impairing Frizzled4 binding are linked to Norrie disease. Furthermore, we developed a high-affinity nanobody that blocks both Norrin and RSPO binding to LGR4, providing a potential tool for therapeutic intervention. These findings elucidate the structural basis of LGR4’s dual signaling roles and lay the groundwork for therapeutic strategies targeting Wnt-related diseases.